Clinical Characteristics and Visit Patterns of Hidradenitis Suppurativa Patients: A Retrospective Cohort Study (Graduate Medical Scholars Journal, 2025)
This retrospective cohort study characterizes clinical features, comorbidities, and care utilization patterns among adult patients with hidradenitis suppurativa (HS) treated at Dartmouth-Hitchcock Dermatology between 2010 and 2023. Data from 409 of 1,124 eligible charts were reviewed, capturing demographics, disease site distribution, comorbid conditions, and dermatology visit frequency. The inguinal folds (59.2%) and axillae (40.8%) were the most commonly affected anatomical regions. Obesity (55.5%), psychiatric disorders (48.4%), and atopic disease (24.9%) were frequent comorbidities, underscoring the systemic burden of HS. Patients averaged four HS-related dermatology visits, with substantial variability in follow-up, suggesting inconsistent long-term disease management. Social history revealed notable tobacco and alcohol use. Early findings reinforce the multifactorial nature of HS and the need for multidisciplinary care. As full data collection continues, future analyses will examine predictors of disease severity, treatment response, missed appointments, and quality-of-life outcomes, ultimately informing improved management guidelines for HS patients in rural New England.